(3OjhGf GHf GdQhejs - (3Ydj Hf GdYHGS Hf LQjL, Ch LhQLjS, GdQhej, CHh GdMSf,J (B283 (3g` s
(3ChdgG (B:s
(3MQa GdgeRI hGdCda(B: (3dhdG ahGcg Cjdhd EPG ELJeYJ ef cd fhY hQb GdLh hGdeGA s
(3BNQgG (B:s
(3eHJhQ hJfJgj Hbhdg(B: (3dh Cf NOj cGf CgdkG dg hGSJgOaJ dj dJgOaJgG s
(3fSNI KGdKIs
(3hQO GjVG JMJ Qbe (B2191s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B297 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B114s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B110 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B766s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs